Business economics in a post-truth era. Issue 4 (October 2017) - Mackintosh, Stuart
Abstract Business economists face increasing challenges at this political and policymaking juncture. "Experts" and economists are out of favor with the public and with certain policymakers. In response, business economists should be frank about our failures and the limits of our models. We can then be ready to defend truth against falsehood. In our defense of fact-based decision making, we must first assert that data matter, and the unbiased integrity of that data matters. We must support and defend the work of the Bureau of Economic Analysis, the Bureau of Labor Statistics, and the Census Bureau. Business economists must be story tellers, transmitting historical memory of past crises, of past attacks on our profession and data sources (such President Nixon's targeting of the Bureau of Labor Statistics).